ИЗ ИСТОРИИ ФОРМИРОВАНИЯ РУССКОЙ ГРАФИКИ И ОРФОГРАФИИ - Вязикова, Лариса (Studia Rossica Posnaniensia, 2008)
The 15th century is a difficult period in the history of Russian writing. It is the period of the development of new graphic and spelling norms, caused by the re-establishment of Old Slavonic. Consequently, in the Russian written records of the 15th century appeared Greek characters as it had happened earlier in the 11th century to the texts copied from Old Slavonic sources. Some of them had since been widely used in Russian writing and existed till the reform of 1918. The orthography of the 15th century is also characterized by certain new features connected with the decay of reduced vowels. Some of these innovations have become the codified forms of modem writing.